1998
DOI: 10.1007/s004380050893
|View full text |Cite
|
Sign up to set email alerts
|

Interallelic complementation at the pyrF locus and the homodimeric nature of orotate phosphoribosyltransferase (OPRTase) in Mucor circinelloides

Abstract: Using 5-fluoroorotic acid (5-FOA) as a positive selection system we isolated mutants of Mucor circinelloides altered in the pyrimidine biosynthetic pathway. These mutants were found to be deficient either in orotidine-5'-monophosphate decarboxylase (OMPdecase), or in orotate phosphoribosyltransferase (OPRTase) activity. Complementation tests among mutants lacking OPRTase activity classified them into three groups, thus suggesting the possibility of interallelic complementation. To investigate this hypothesis a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Plasmid pAVB89, carrying both the genomic copy of the gene encoding phytoene dehydrogenase and the gene pyrF (Velayos et al 1998) of M. circinelloides, was used to transform to prototrophy three dierent carB, pyrF mutant strains of M. circinelloides (MS33, MS43 and MS46). As the transformants are obtained as heterokaryons, they were subjected to three cycles of vegetative growth, and a single colony from two dierent transformants of each strain was selected for further analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Plasmid pAVB89, carrying both the genomic copy of the gene encoding phytoene dehydrogenase and the gene pyrF (Velayos et al 1998) of M. circinelloides, was used to transform to prototrophy three dierent carB, pyrF mutant strains of M. circinelloides (MS33, MS43 and MS46). As the transformants are obtained as heterokaryons, they were subjected to three cycles of vegetative growth, and a single colony from two dierent transformants of each strain was selected for further analysis.…”
Section: Resultsmentioning
confidence: 99%
“…The E. coli strains were grown in Luria broth (LB; Sambrook et al 1989), appropriately supplemented. Mucor circinelloides wild-type strain CBS277.49 (CBS; Centraalbureau voor Schimmelcultures, Baarn, The Netherlands) and carB mutants MS33, MS43 and MS46 (Velayos et al 1997(Velayos et al , 1998 were used. Minimal medium YNB [1% glucose, 0.05% yeast nitrogen base without amino acids, 0.15% (NH 4 ) 2 SO 4 , 0.15% glutamic acid] and complete medium YPG [0.3% yeast extract, 1% peptone, 2% glucose] were used and uracil (400 lg ml )1 ) was added when needed.…”
Section: Methodsmentioning
confidence: 99%
“…Labelling, hybridization and immunological detection were carried out using the digoxigenin (DIG)‐based ‘Nonradioactive labeling and immunological detection kit’ and the ‘PCR DIG labeling mix’ (Roche Molecular Biochemicals) following the supplier's recommendations. Oligonucleotides FSALELOS1 (5′‐GGCGACAGTAGCAATGGCGACGATTTAC‐3′), complementary to nucleotide positions +2215 to +2242 in the 3′ noncoding region of the carRP gene, and FSALELOS2 (5′‐GTGATGGATCAAGGAGCAGCGGCC‐3′), corresponding to positions +138 to +118 of the carB gene, were used for allele amplification under conditions described previously [32], except that the annealing temperature was 68 °C, and 35 cycles were performed. Oligonucleotides FSS1 (5′‐CATTCCACGACCTGTCCG‐3′), positions +915 to +932 of the carRP gene, and FSI1 (5′‐CCTTGACAATGGCTGGGC‐3′), positions +1695 to +1678, were used for probe PCR labelling.…”
Section: Methodsmentioning
confidence: 99%
“…Self-replicative transformation seems to prevail, in contrast with the predominance of integrative transformation in other fungi (Fincham, 1989). The best results are obtained with Mucor circinelloides, an obscure organism until it was found that it is transformable at high rates, about 1 transformed colony per ng DNA and 10 6 spheroplasts, and that many of its gene sequences support self replication of plasmids (Benito et al, , 1995Heeswijck and Roncero, 1984;Heeswijck, 1986;Iturriaga et al, 1992;Ruiz-Hidalgo et al, 1999;Velayos et al, 1998). The transformed phenotype is much less frequent and very unstable in Absidia glauca (Burmester, 1995;Burmester et al, 1992;W€ o ostemeyer et al, 1987), Parasitella simplex (Burmester, 1992), Rhizopus niveus (Takaya et al, 1996), Rhizopus oryzae (Skory, 2002), and Phycomyces blakesleeanus (see below).…”
Section: Introductionmentioning
confidence: 99%